This preview shows page 1. Sign up to view the full content.
Unformatted text preview: 2 , we have ( ax-bx 2 ) v + v x = axv-bx 2 v + v x = a-bx + v x = 0 since xv = 1 So a-bx + v x = 0 (7) Divide (7) by x and notice 1 x is v , we have v + av-b = 0 , or v + av = b. Apply the solution formula for linear equation we have v = e-R adt Z be R adt dt + C ! So x = 1 v = e R adt R be R adt dt + C ! a Example 3.4 . In the logistic model, dx dt = ax-bx 2 , suppose a > ,b > are constants, we will discuss behavior of the solutions....
View Full Document
This note was uploaded on 10/04/2011 for the course MAP 4231 taught by Professor Dr.han during the Spring '11 term at UNF.
- Spring '11